Functional Movement Screening: An Early Detection of The Student Injury Risk in Sport Class - Syafei, Muhamad; Budi, Didik Rilastiyo; Listiandi, Arfin Deri; Festiawan, Rifqi; Kusnandar, Kusnadar; Nurcahyo, Panuwun Joko; Stephani, Mesa Rahmi; Qohhar, Wildan (Universitas Pendidikan Indonesia, 2020)
Physical Education class is one of the solutions taken by regional schools to improve achievements in sports. The process of recruiting physical education class students has mostly conducted by using Â the talent scouting test method which consists of physical test and skill test. However, the implementation of sport injury detection test using Functional Movement Screening (FMS) is still insignificant. The purpose of this study was to identify the student risk of injury in physical education class by using the FMS test. The research was an ex-post-facto method. The research samples were 32 Â students of class VIII in the physical education class at SMPN 1 Baturaden (20 males and 12 females) aged 14 years in average. The research instrument used was the Functional Movement Screening (FMS) test with the validity and reliability of 0.81. Data processing and analysis employed the Benchmark Reference (PAN) with the help of Ms. Excel. The results showed that 56.25% of physical education class students at SMPN 1 Baturaden were identified at risk of sports injuries. The results also showed an imbalance of strength between the right and left body muscles. The study Â concludes that the use of Functional Movement Screening (FMS) test is important to minimize the high likelihood of injury of the students in physical education class.